MACEDONIAN ACCESSION IN THE UN - Marolov, Dejan (European Scientific Journal, ESJ, 2014)
The process of the Macedonian accession in the United Nations is quite controversial. Namely, this accession was a unique example in the UN history. Macedonia has become a UN member under special and additional preconditions. This had and still has big implications on the Macedonian state. This paper is treating this issue by analyzing legal-political texts and another appropriate literature. The paper suggests that the UN accession was more than necessary for Republic of Macedonia but in the same time it was very controversial for both, Republic of Macedonia and the UN.